PENDEKATAN UNDERSTANDING BY DESIGN SEBAGAI STRATEGI PENGEMBANGAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Sariyanti, Sariyanti; Indarwati, Dwi; Darmawan, Indra (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
This article discusses the Understanding by Design (UbD) approach, which focuses on designing learning by starting with the desired goals, then determining the evaluation methods, and finally planning the steps of instruction. This approach, known as Backward Design, differs from other instructional design methods that typically place assessment at the end of the learning process. UbD consists of three main stages: 1) identifying desired results, 2) determining acceptable evidence, and 3) planning learning experiences and instruction. The first stage involves formulating learning goals based on the needs of the learners. In the second stage, assessments are designed to align with the learning goals, providing important feedback for both students and teachers. The third stage involves planning and executing effective learning activities, with the teacher playing a crucial role in creating engaging learning experiences. The implementation of UbD within the Merdeka Curriculum demonstrates that this approach supports the quality of education by focusing on student-centered learning, enhancing engagement and motivation, and facilitating more targeted instruction. This article aims to provide guidance and references for teachers in applying the UbD approach in the learning process, thereby advancing education in Indonesia.